Application and Analysis of Orbital Angular Momentum Technology in Optical Communication - Junsen Lai; Bingbing Wu; Wenyu Zhao; Haiyi Zhang (Dianxin kexue)
Orbital angular momentum, which is considered as a promising solution for future improvement of optical network capacity, has become a research focus in ultra-high speed optical communication. The principle and latest research progress of orbital angular momentum technology in optical communication were reviewed; the challenges and application prospect of the technology were also analyzed.